2019
DOI: 10.1186/s12884-019-2628-5
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of influenza vaccination uptake in pregnancy: a large single-Centre cohort study

Abstract: BackgroundAlthough vaccination of pregnant women against influenza is recommended, the vaccination rate remains low. We conducted a study to identify determinants of influenza vaccination uptake in pregnancy in order to identify strategies to improve seasonal influenza vaccination rates.MethodsProspective observational hospital-based study in the French hospital performing the highest number of deliveries, located in the city of Lille, among all women who had given birth during the 2014–2015 influenza season. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 23 publications
3
27
1
Order By: Relevance
“…Campaigns directed at pregnant women to be vaccinated against influenza are needed. Bartolo et al (2019) found that 35.5% of the 2045 pregnant women in their study reported they had been vaccinated against influenza during their pregnancy; the factor significantly associated with vaccination uptake was previous influenza vaccination. Other influences included, to a lesser degree, were first pregnancy, history of preterm birth, the mother's knowledge of the influenza vaccine (and the perception that complications associated with the vaccine were low).…”
Section: Maternal Diseasementioning
confidence: 86%
See 3 more Smart Citations
“…Campaigns directed at pregnant women to be vaccinated against influenza are needed. Bartolo et al (2019) found that 35.5% of the 2045 pregnant women in their study reported they had been vaccinated against influenza during their pregnancy; the factor significantly associated with vaccination uptake was previous influenza vaccination. Other influences included, to a lesser degree, were first pregnancy, history of preterm birth, the mother's knowledge of the influenza vaccine (and the perception that complications associated with the vaccine were low).…”
Section: Maternal Diseasementioning
confidence: 86%
“…Possibly more worrying for the premature baby is those who were born during influenza season had a significantly higher risk of periventricular leukomalacia, a brain injury that creates holes in the white matter ( Härtel et al, 2016 ). The World Health Organization (WHO) has recommended influenza vaccination for all pregnant women since 2012, but the vaccination rate has been low ( Bartolo et al, 2019 ).…”
Section: Infection/inflammationmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have tried to determine the factors in uencing coverage of vaccination against in uenza during pregnancy. Different authors have highlighted that vaccination recommendation by health professionals is the main reason why pregnant women chose to be vaccinated against in uenza [16][17][18][19][20]. Other studies have identi ed additional in uences such as: socio-economic characteristics, fear of side effects, doubts about the safety and effectiveness of the vaccine, fear of needles/pain or under-estimation of personal risk [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%